2022
DOI: 10.1002/nme.6934
|View full text |Cite
|
Sign up to set email alerts
|

Local non‐intrusive reduced order modeling based on soft clustering and classification algorithm

Abstract: The use of non-intrusive reduced order modeling (NIROM) to approximate high-fidelity computer models has been steadily increased over the past decade. Recently, local NIROM has been proposed to improve the model accuracy in highly nonlinear problems in which distinct characteristic regimes coexist. The core concept of local NIROM is the decomposition of the parameter domains into a subregime to create multiple models. However, the existing local NIROM not only partitions the individual models in a mutually exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…i T means the travel time of the user in data i , and i D indicates the travel distance of the user in data i . For the extraction of clustering features, the k-means clustering algorithm is used in the study [31]. To normalize traffic data, the Z-score method [32] is used in the study, and its calculation is shown in equation (12).…”
Section: A Design Of User Travel Patterns Recognitionbased On DLmentioning
confidence: 99%
“…i T means the travel time of the user in data i , and i D indicates the travel distance of the user in data i . For the extraction of clustering features, the k-means clustering algorithm is used in the study [31]. To normalize traffic data, the Z-score method [32] is used in the study, and its calculation is shown in equation (12).…”
Section: A Design Of User Travel Patterns Recognitionbased On DLmentioning
confidence: 99%
“…A two-dimensional (2D) transonic flow problem, which is not only practical for evaluating the airfoil performance, but is also a benchmark problems that is widely used in previous ROM studies [11,10,8,21], is examined in this study. The transonic flow field is generated by the KFLOW finite-volume-based CFD solver [38,39].…”
Section: Data Preparationmentioning
confidence: 99%